2017
DOI: 10.1002/adhm.201601286
|View full text |Cite
|
Sign up to set email alerts
|

Methotraxate‐Loaded Hybrid Nanoconstructs Target Vascular Lesions and Inhibit Atherosclerosis Progression in ApoE−/− Mice

Abstract: Atherosclerosis is an inflammatory disorder characterized by the progressive thickening of blood vessel walls eventually resulting in acute vascular syndromes. Here, intravenously injectable hybrid nanoconstructs are synthesized for tempering immune cell inflammation locally and systemically. Lipid and polymer chains are nanoprecipitated to form 100 nm spherical polymeric nanoconstructs (SPNs), loaded with methotrexate (MTX) and subsequently labeled with Cu and fluorescent probes for combined nuclear/optical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…50 UTMD has proved to be an effective delivery method for miRNA mimics, as well as other gene-targeting strategies in experimental in vivo studies. [51][52][53][54] Our present results indicate successful use of UTMDenhanced delivery of miR-21 mimics into the carotid artery to rescue vulnerable plaques, while not exerting off-target effects in the liver, the prototypical organ in which antisense oligonucleotides are known to assimilate. Future studies should test if the delivery strategy of UTMD-enhanced miR-21 modulation could be applied not only in carotid arteries but also in the coronary system, as well as other advanced atherosclerotic lesion sites prone to rupture.…”
Section: Discussionmentioning
confidence: 59%
“…50 UTMD has proved to be an effective delivery method for miRNA mimics, as well as other gene-targeting strategies in experimental in vivo studies. [51][52][53][54] Our present results indicate successful use of UTMDenhanced delivery of miR-21 mimics into the carotid artery to rescue vulnerable plaques, while not exerting off-target effects in the liver, the prototypical organ in which antisense oligonucleotides are known to assimilate. Future studies should test if the delivery strategy of UTMD-enhanced miR-21 modulation could be applied not only in carotid arteries but also in the coronary system, as well as other advanced atherosclerotic lesion sites prone to rupture.…”
Section: Discussionmentioning
confidence: 59%
“… 14 , 15 For instance, MTX-loaded polymeric nanoparticles were shown by the authors to mitigate atherosclerotic progression in apolipoprotein-E (apoE) −/– mice, fed with a high-fat diet (HFD). 16 Indeed, accumulation of blood-borne nanoparticles into atherosclerotic plaques would increase the dose of MTX delivered specifically to the inflamed arterial wall, avoiding side effects associated with systemic exposure. Nanoparticle accumulation is supported by different and multiple mechanisms, including the direct nanoparticle uptake by phagocytic macrophages; 17 19 the deposition within the diseased tissue due to favorable, local hydrodynamic conditions (recirculation area and low wall shear stresses), hyper-permeability of a dysfunctional endothelium and increased angiogenesis; 20 24 the direct plaque localization via molecular targeting; 25 28 and the nanoparticle uptake by circulating monocytes that would eventually infiltrate the plaque.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar approach, Stigliano et al ( 2017 ) confirmed the potentiality of MTX in preventive-oriented treatments by loading it into NPs. The authors demonstrated specific accumulation of NPs into macrophages residing within lipid-rich plaques along the arterial tree.…”
Section: Nps For As Treatment and Diagnosismentioning
confidence: 96%
“…Drug-loaded NPs targeting macrophages and other immune cells could control their pro-inflammatory activities and thus prevent, attenuate, and possibly reverse related disorders (i.e., increased atherosclerosis, but also altered adipocyte function and insulin resistance). At the same time, NPs could also be loaded with imaging agents allowing the detection of vulnerable atherosclerotic plaques; similar theranostic strategies already showed potential for detection and treatment of other diseases (including cancer and neurodegenerative disorders), exploiting a number of imaging modalities, among which optical imaging (OI), magnetic resonance imaging (MRI), ultrasound and photoacoustic (US-PA), computed tomography (CT), and nuclear imaging based on single photon and positron emission tomography (SPECT, PET; Xie et al, 2010 ; Kim et al, 2014 ; Weissleder et al, 2014 ; Atukorale et al, 2017 ; Stigliano et al, 2017 ; Zhang et al, 2017 ).…”
Section: Toward Targeted Theranostics Npsmentioning
confidence: 99%